World War II, Missing Men and Out of Wedlock Childbearing*. (8th August 2012) - Bethmann, Dirk; Kvasnicka, Michael
<x xml:space="preserve">Abstract</x> Drawing upon county‐level census data for the German state of Bavaria in 1939 and 1946, we use World War II (WWII) as a natural experiment to study the effects of changes in the adult sex ratio on out of wedlock fertility. Our findings show that war‐induced shortfalls of men significantly increased the non‐marital fertility ratio in the middle of the century. Furthermore, we find that the regional magnitude of this effect varies with the county‐level share of prisoners of war (POWs) in an inverse manner. Unlike military casualties and soldiers missing in action, POWs had a sizeable positive probability of returning home from the war. It appears therefore that both current marriage market conditions and foreseeable improvements in the future marriage market prospects of women influenced fertility behaviour in the immediate aftermath of WWII.